Mind the Gap: It’s About Digital Maturity, Not Technology - Yılmaz, Kemal Özkan (IGI Global, 2021)
The Covid-19 pandemic has amplified the influence of digital transformation on business entities. Although it is becoming more feasible to invest in digital technologies due to their swift progression in terms of reaching higher technical capabilities and better pricing levels; some companies some companies could not achieve expected improvements in their business results. On the contrary, a remarkable number of companies had the opportunity to develop their businesses by leaps and bounds. Academic research on the subject revealed that a company's digital maturity level is directly related to the company's success and progress in sustainability issues. In this chapter, the concepts of crossfunctional collaboration and corporate digital cultures, which are the basic components of achieving digital maturity, which must be coordinated together, are elaborated and an applicable roadmap proposal is tried to be created.
Keywords: Accepting Failures; Cross-Functional Collaboration; Organizing Around the Customer; Corporate Digital Cultures; Collaboration Dynamics; New Ways of Engagement; New Working Styles; Organizational Flexibility; Reorganizing Organizational Boundaries; Risk-Tolerant Culture